The effects of IL-27 and IL-35 gene variation and expression levels on the susceptibility and clinical manifestations of pulmonary tuberculosis - Gao, Lei; Xiong, Yan-Jun; Liang, Ya-Xue; Huang, Peng-Fei; Liu, Shuang; Xiao, Yu; Huang, Qian; Wang, Hua; Wu, Hui-Mei (Frontiers in Immunology, 2024)
Inflammatory cytokines have crucial roles in the pathogenesis of tuberculosis (TB), and interleukin (IL)-27 and IL-35 have a pro-inflammatory and anti-inflammatory effect on many diseases, including infectious diseases. Therefore, we evaluated the relationship between IL-27 and IL-35 gene polymorphism, expression levels, and pulmonary TB (PTB) susceptibility. Nine single-nucleotide polymorphisms (SNPs) in the IL-27 gene (rs181206, rs153109, and rs17855750) and the IL-35 gene (rs4740, rs428253, rs9807813, rs2243123, rs2243135, and rs568408) were genotyped by the SNPscan technique in 497 patients with PTB and 501 controls. There was no significant difference regarding the genotype and allele frequencies of the above SNPs in the IL-27 and IL-35 genes between patients with PTB and controls. Haplotype analysis showed that the frequency of the GAC haplotype in the IL-35 gene was significantly decreased in patients with PTB when compared to controls (p = 0.036). Stratified analysis suggested that the frequency of the IL-27 rs17855750 GG genotype was significantly increased in patients with PTB with fever. Moreover, the lower frequency of the IL-35 rs568408 GA genotype was associated with drug-induced liver injury in patients with PTB. The IL-35 rs428253 GC genotype, as well as the rs4740 AA genotype and A allele, showed significant relationships with hypoproteinemia in patients with PTB. When compared with controls, the IL-27 level was significantly increased in patients with PTB. Taken together, IL-35 gene variation might contribute to a protective role on the susceptibility to PTB, and IL-27 and IL-35 gene polymorphisms were associated with several clinical manifestations of patients with PTB.